Crowdsourcing framework applied to strategic digital city projects - Carla Cavichiolo Flores; Denis Alcides Rezende (Journal of Urban Management, 2022)
If strategically implemented, crowdsourcing helps capture the intelligence of a variety of e-participation actors, enabling them to share the leading role with the government in decision-making processes. The objective is to elaborate an original crowdsourcing framework applied to strategic digital city projects. The research methodology is exploratory and descriptive. On the one hand, the model supports a systematic analysis of empowerment degrees of the e-participation actors to initiate task and innovation-oriented spontaneous crowdsourcing activities for solving wicked problems. On the other hand, strategic digital city projects play the role of passively monitoring spontaneous crowdsourcing activities, and actively planning and implementing government initiatives. The conclusion shows that the framework can encourage local governments to identify talents, influencers, and partners among different stakeholders - to discover what motivates them to participate and the rewards they expect - thus evolving strategies to welcome innovative projects, processes, products, and ideas in a continuous learning cycle.
Keywords: 710; Collective decision; Crowdsourcing; e-governance; e-participation; Social platforms; Strategic digital city projects